Extrakapsulární zlomeniny proximálního femuru – retrospektivní vyhodnocení souboru pacientů se zaměřením na komplikace léčby - Novotný, P; Dědek, T; Frank, M; Šmejkal, K; Bútora, S; Kočí, J; Trlica, J (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2018)
PURPOSE OF THE STUDY The purpose of this study is to retrospectively evaluate the treatment and the complications in patients with extracapsular proximal femoral fractures. MATERIAL AND METHODS The evaluation focused on a group of patients who underwent a surgery at the authors department in the period from 1 January 2011 to 31 December 2013. The inclusion criteria were a simple fall and a monotrauma. The injury-to-surgery interval, course of the surgery and hospital stay, occurrence of early and late complications were assessed. RESULTS In the respective period 286 patients underwent surgery, with the mean age of 79 years (36-101). A basicervical fracture was suffered by 20 patients, a pertrochanteric fracture by 228 patients and 38 patients sustained a subtrochanteric fracture. Osteosynthesis using the DHS was applied in 113 patients, in 110 patients PFNA osteosynthesis was performed and in 51 patients osteosynthesis using an Ender nail was conducted. Yet another type of plate osteosynthesis was opted for in 12 patients. The most frequent postoperative complication was delirium, which was reported in a total of 38 patients. Non-infectious early seroma and hematoma type collection was observed in 6 patients. An infection occurred in one patient. Apart from 8 patients who died during the primary hospital stay, the fracture healing was followed up in 252 patients (91% of 278). The length of healing was 15 weeks on average, delayed healing was reported in five patients. Primary malposition was seen in 9 patients (3%) and secondary malposition occurred in five patients (2%). There were five cases of non-union (2% of 278) in our group of patients. In the followed-up period, a total of 86 patients (30 % of 286) died within one year after the injury. In cases of death, the follow-up was 100% thanks to the data obtained from the Institute of Health Information and Statistics of the Czech Republic (UZIS). Death as a direct consequence of proximal femur fracture occurred in 66 patients (23% of 286). DISCUSSION The results of complications in our group (infection, delayed healing, malposition and non-union) are comparable to those identified by other authors, with the exception of one-year lethality, which is lower in the presented group. CONCLUSIONS The occurrence of complications after proximal femur surgeries is affected by multiple factors. The most important are the choice of a suitable implant, technically correct execution of osteosynthesis and intensive postoperative treatment, including the continuity of care after hospital discharge. Key words:extracapsular proximal femoral fractures, complications.
Keywords: senioři; delirium; fraktury krčku femuru; Femoral Neck Fractures; hematom; Retrospective Studies; Česká republika; fraktury femuru; Bone Malalignment; mužské pohlaví; Fracture Fixation, Internal; Czech Republic; Hematoma; Postoperative Complications; kostní destičky; Delirium; ženské pohlaví; retrospektivní studie; Humans; hojení fraktur; vnitřní fixace fraktury; Bone Plates; Femoral Fractures; Female; Aged; subluxační postavení kloubu; pooperační komplikace; lidé; Male; Fracture Healing